T Cell Bispecific Antibodies: An Antibody-Based Delivery System for Inducing Antitumor Immunity - Daisuke Kamakura; Ryutaro Asano; Masahiro Yasunaga (MDPI AG, 2021)
As a breakthrough immunotherapy, T cell bispecific antibodies (T-BsAbs) are a promising antibody therapy for various kinds of cancer. In general, T-BsAbs have dual-binding specificity to a tumor-associated antigen and a CD3 subunit forming a complex with the TCR. This enables T-BsAbs to crosslink tumor cells and T cells, inducing T cell activation and subsequent tumor cell death. Unlike immune checkpoint inhibitors, which release the brake of the immune system, T-BsAbs serve as an accelerator of T cells by stimulating their immune response via CD3 engagement. Therefore, they can actively redirect host immunity toward tumors, including T cell recruitment from the periphery to the tumor site and immunological synapse formation between tumor cells and T cells. Although the low immunogenicity of solid tumors increases the challenge of cancer immunotherapy, T-BsAbs capable of immune redirection can greatly benefit patients with such tumors. To investigate the detailed relationship between T-BsAbs delivery and their T cell redirection activity, it is necessary to determine how T-BsAbs deliver antitumor immunity to the tumor site and bring about tumor cell death. This review article discusses T-BsAb properties, specifically their pharmacokinetics, redirection of anticancer immunity, and local mechanism of action within tumor tissues, and discuss further challenges to expediting T-BsAb development.